PHYTOCHEMICAL SCREENING AND DETERMINATION OF ANTIOXIDANT ACTIVITY OF Helicia nilagirica Bedd., AN ETHNOMEDICINAL PLANT OF MIZORAM, INDIA - PC, LALAWMPUII; C, Malsawmtluangi; Zothanpuia; Bb, Kakoti (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Â Â Objectives: The present study was undertaken to screen the phytochemical constituents and determine the antioxidant activity of Helicia nilagirica Bedd., an ethnomedicinal plant of Mizoram, India. Methods: Phytochemical screening was carried out according to standard procedures on the methanolic bark extract of the plant. The methanolic extract was subjected to in-vitro screening models such as DPPH radical scavenging assay, hydroxyl scavenging activity assay and reducing power assay using BHA and ascorbic acid respectively as standards. The total phenolic and total flavonoid content were determined using Gallic acid and Quercetin respectively as standards. Results: The presence of flavonoids, glycosides, steroids and carbohydrates was indicated by the tests conducted. The methanol extract exhibited IC50 values of 3.92 Î¼g/ml and 6.86 Î¼g/ml respectively in DPPH and hydroxyl radical scavenging activity assay. The reducing power of the extract was lower than that of the standard ascorbic acid. The total phenolic content and flavonoid content was 62.75 mg/g and 56 mg/g of gallic acid and quercetin equivalent respectively. Conclusion: The results of the present study concluded that the methanolic extract of the bark of Helicia nilagirica Bedd. possess antioxidant activity. Keywords: Helicia nilagirica, Phytochemicals, Antioxidant activity, Diphenyl-1-picrylhydrazyl, Phenol and flavonoid.